Recall and Precision Devices in IRRD Thesaurus - Ragavan, M. C.; Srivastava, M. K.; Gupta, S. P. (Journal of Information and Knowledge, 1983)
Giving breif description of the International Road Research Documentation (IRRD) Thesaurus, the paper examines the recall and precision devices incorporated in the thesaurus. for storage and retrieval of Highway Engineering information. The role of the "arrowed-diagrams" a special feature of the thesaurus, in indexing and retrieval of information is highlighted.